Itraconazole as a new pharmacotherapy method in haemangiomas - Gałązka, Przemysław; Leis, Kamil; Mazur, Ewelina; Nowowiejska, Laura (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Early childhood haemangioma ranks as one of the most common childhood neoplasms. This type of birthmark occurs in about 5% of all infants, most often during the first through fifth months of age. These benign tumours can develop in both internal organs (e.g., the liver) and on the skin, which is a particularly frequent location [1]. Currently, the standard of treatment is pharmacotherapy with beta blockers. Propranolol is the most commonly prescribed beta blocker due to its high efficacy and safety profile confirmed by many studies. As an alternative, other beta blockers can be used, including atenolol, timolol, and imiquimod [1–3]. In case of no satisfactory effect after pharmacotherapy, laser therapy or surgical treatment may be recommended [1, 2].